GIADA performance during Rosetta mission scientific operations at comet 67P. Issue 8 (15th October 2018) - Sordini, R.; Della Corte, V.; Rotundi, A.; Rotunno, S.; Ferrari, M.; Ivanovski, S.L.; Colangeli, L.; Palumbo, P.; Lopez-Moreno, J.J.; Rodriguez, J.; Fulle, M.; Green, S.F.; et al.
Highlights: We report on the performance of GIADA, an instrument onboard Rosetta designed to study the 67P/CG coma dust environment. Dust contamination of the Grain Detection System (GDS), a GIADA subsystem, did not prevent its nominal operations. GDS temperature dependence did not add error in the particle cross-section measurements. During the first 15 months of measurements at comet 67P/CG GIADA operated nominally. Abstract: The Grain Impact Analyser and Dust Accumulator (GIADA) instrument onboard Rosetta studied the dust environment of comet 67P/Churyumov–Gerasimenko from 3.7 au inbound, through perihelion, to 3.8 au outbound, measuring the dust flow and the dynamic properties of individual particles. GIADA is composed of three subsystems: (1) Grain Detection System (GDS); (2) Impact Sensor (IS); and (3) Micro-Balances System (MBS). Monitoring the subsystems' performance during operations is an important element for the correct calibration of scientific measurements. In this paper, we analyse the GIADA inflight calibration data obtained by internal calibration devices for the three subsystems during the period from 1 August 2014 to 31 October 2015. The calibration data testify a nominal behaviour of the instrument during these fifteen months of mission; the only exception is a minor loss of sensitivity for one of the two GDS receivers, attributed to dust contamination.